Peningkatan Hasil Belajar Pendidikan Matematika Melalui Model Pembelajaran Kooperatif Tipe (TGT) pada Siswa Kelas IVdi SDN 12 Mataram Tahun Ajaran 2024/2025 - Dedy Kusnaeni; Amrullah; Dika Areka (Mataram University, 2026)
This study aimed to improve students’ mathematics learning outcomes through the implementation of the Teams Games Tournament (TGT) cooperative learning model in fourth-grade students at SD Negeri 12 Mataram during the 2024/2025 academic year. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consisted of two cycles. Each cycle included four stages: planning, implementation, observation, and reflection. The research subjects consisted of 14 students. Data were collected through pre-tests, post-tests, and observation sheets. The findings revealed that before the implementation of the TGT cooperative learning model, the average student score was 59.1, with only 14.3% of students achieving the Minimum Mastery Criteria (KKM). After the implementation of the TGT model, the average score increased to 83.2, and 92.2% of students successfully achieved the KKM. The improvement indicated that the TGT cooperative learning model effectively enhanced students’ conceptual understanding and participation in mathematics learning. The success of this model was supported by active learning activities that encouraged students to think critically, collaborate, and engage in group discussions. Therefore, the TGT cooperative learning model is recommended as an effective strategy to improve mathematics learning outcomes in elementary schools.